2020
DOI: 10.1101/2020.06.25.20140384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of Antibodies to SARS-CoV-2 in Six Sites in the United States, March 23-May 3, 2020

Abstract: Importance: Reported cases of SARS-CoV-2 infection likely underestimate the prevalence of infection in affected communities. Large-scale seroprevalence studies provide better estimates of the proportion of the population previously infected. Objective: To estimate prevalence of SARS-CoV-2 antibodies in convenience samples from several geographic sites in the United States. Design: Serologic testing of convenience samples using residual sera obtained for routine clinical testing by two commercial laboratory c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
124
2
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 18 publications
13
124
2
3
Order By: Relevance
“…Other modeling work ( 16 ) suggests that the feasibility of containing SARS-CoV-2 is highly sensitive to the number of infections that occur prior to initiation of containment efforts. Our estimate that fewer than 10% of local symptomatic infections were detected by surveillance for around a month is consistent with estimates from a serological study ( 36 ) and suggests that a crucial opportunity to limit the impact of SARS-CoV-2 on the United States may have been missed. Although the number of tests administered increased in March ( 9 ), so too did the number of infections and consequently, the demand for testing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Other modeling work ( 16 ) suggests that the feasibility of containing SARS-CoV-2 is highly sensitive to the number of infections that occur prior to initiation of containment efforts. Our estimate that fewer than 10% of local symptomatic infections were detected by surveillance for around a month is consistent with estimates from a serological study ( 36 ) and suggests that a crucial opportunity to limit the impact of SARS-CoV-2 on the United States may have been missed. Although the number of tests administered increased in March ( 9 ), so too did the number of infections and consequently, the demand for testing.…”
Section: Discussionsupporting
confidence: 86%
“…Although other approaches—namely, serological surveys—could have provided more direct answers to the question of how many unobserved infections there were in the weeks following the arrival of SARS-CoV-2 in the United States, serological assays were only beginning to be developed at that time ( 35 ). Even now that results from serological surveys are beginning to emerge ( 36 ), they still do not address the extent of unobserved infections during the specific time frame of our analysis, are not representative of the United States as a whole, and can be sensitive to even small inaccuracies in assay performance ( 37 , 38 ). Relative to other approaches, our approach offers the ability to quickly obtain provisional estimates of the number of unobserved infections early in an epidemic, when there still might be time to act on that information with testing and case isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Are these low levels of case detection reasonable? For countries where per capita testing is over 100-fold higher than in Madagascar (79.1/100,000 population in July 2020), it is estimated that less than 10% of COVID-19 cases have been detected [ 29 ]. Though the precise case detection rates for Madagascar cannot be discerned from available data, there are a number of indicators suggesting that these are lower than the already low rates of Europe or the US.…”
Section: Case Detectionmentioning
confidence: 99%
“…For different countries around the world, several researchers [1][2][3][4][5][6][7] have concluded that the number of people actually infected, or affected, by COVID-19 is far greater than the number of cases actually reported, or detected officially. Recent serological surveys for COVID-19 also indicate that the infected people outnumber detected people by about 12 times in Spain 8 and 6 to 24 times in the USA 9 . Other serological surveys suggest that about 18% of people in London 10 and 23% of the people in New Delhi 11 were already infected by mid-April and early July, respectively, far outnumbering the reported cases.…”
Section: Introductionmentioning
confidence: 99%